IMPLEMENTATION OF THE EXTREME PROGRAMMING METHOD IN DESIGNING AN INFORMATION SYSTEM FOR APPLYING FOR PHARMACIST PRACTICE LICENSES AT PTSP TAMANSARI DISTRICT, WEST JAKARTA - Rudianto, Biktra; Jayanti, Dede (Journal of Information System, Informatics and Computing, 2023)
The West Jakarta One-Stop Integrated Service Unit (PTSP Jakarta Barat) is a West Jakarta government institution that serves the needs and interests of the community, particularly pharmacists who handle the Pharmacy Practice License (SIPA) service. However, to apply for a Pharmacy Practice License (SIPA), one must visit the West Jakarta PTSP office in person, and the current registration system still utilizes paper for pharmacist data entry. The development of the SIPA information system can assist pharmacists in applying for a Pharmacy Practice License without having to visit the West Jakarta PTSP office. The method used is object-oriented with structured web modeling, the database utilizes MYSQL, while the application is developed using PHP programming with the assistance of the Laravel framework. The result is a web-based application program that facilitates the process of pharmacist practice licensing services.